Stanovení remdesiviru pomocí vysokoúčinné kapalinové chromatografie s tandemovou hmotnostní detekcí u pacienta s infekcí SARS-CoV-2 - Petrus, Jakub; Grondžák, Tomáš; Čepová, Jana; Dunovská, Kateřina; Hosnedlová, Božena; Beroušek, Jan; Průša, Richard; Kizek, René; Klapková, Eva (Chemické listy, 2022)
One of the officially approved medications for the treatment of the pandemic disease COVID-19, caused by the SARS-CoV-2 virus, is remdesivir. This antiviral mole-cule is a prodrug that is metabolized into its active form (an ATP analogue). Because of its hepatotoxicity and ne-phrotoxicity, it is necessary to monitor the serum concen-trations of remdesivir. For the therapeutic drug monitoring of remdesivir, a method using liquid chromatography with tandem mass spectrometry (LC-MS/MS) in positive elec-trospray ionization mode was developed. Mass detection was done via triple quadrupole in the Multiple reaction monitoring mode. Separation was done on Zorbax C18 column at 35 °C in mobile phase gradient and flow 0.4mLmin–1(A –0.1% formic acid in water, B –0.1% formic acid in 95% acetonitrile). Time of analysis was 4minutes. LC-MS/MS method was successfully validated. Calibration was done in blood serum and plasma and it was linear in the range of tested concentrations (0–1000 ngmL–1). Samples were prepared by protein precipitation. The method was used to measure remdesivir concentration in a patient with SARS-CoV-2 infection. The measured concentration 60 minutes after remdesivir application was 175±15 ngmL–1.
Keywords: Antiviral Agents; remdesivir; Humans; Research Design; lidé; SARS-CoV-2; tandemová hmotnostní spektrometrie; Chromatography, Liquid; výzkumný projekt; chromatografie kapalinová; antivirové látky; Drug Monitoring; Tandem Mass Spectrometry; monitorování léčiv